(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2013)
Introduction. The design rule requirements for abstracts and reports for participate in the International Scientific Technical Conference «Radio Engineering Field, Signals, Devices and Systems» or abbreviated REFSDS are presented at this paper. Requirements for document. The requirements for execution of text, formulas, tables and figures with examples of implementation are expounded. The examples of bibliographic records execution and abstracts are presented. Methods of counteraction to the unauthorized access. The characteristics of the known methods of detecting unauthorized connections to the subscriber telephone line, providing the confidentiality of telephone conversations, protecting from listening of apartments and prevention of the unauthorized use of telephone connection are given. Conclusions. The classification of threats of confidentiality violation in telephone communication channels is conducted and methodology for eliminating of unauthorized interception of information is proposed. The complex use of a number of the listed technical equipments allows to prevent the use of communication channels for the wire tapping and listening of apartments, through which they pass.